(3TQM GdfadjIs - (3eLghds
(3ChdgG (B:s
... (3hbO jchf djS CfHjGA eKd LHQGFjd hejcGFjd hbO jchf CfHjGA eQSjdjf eKd ghO hUGdM hEOQjS hjhfS hfHjfG eMeO Udi Gddg Ydjg hBdg CaVd GdCfHjGA hGdeQSdjf (B...s
(3BNQgG (B:s
... (3bhdg dh cGfJ CQHYG bVi GdMGLI hGdeSGaQ GdNeS JbOjQG dh aGJg CQHY aQGFV aj MVQ jbVj GdUHM ChdG Ke GdXgQ JeGeG Ke GdYUQ JeGeG Ke (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3hba (B:(3YHGS Hf MSjf GdNQSGfj , Ydi (B: (3CMeO ehSi hBNQjf , SfI (B: 1269 (3g`s
Keywords: (3abg GdePGgH GdCNQis